Diversity of Zingiber Mill. (Zingiberaceae) in Peninsular Malaysia Including Short Remarks of an Undescribed Taxon - Sedek, Aimi Syazana; Mohamad, Salasiah; Yen, Sam Yen (Universitas Gadjah Mada, 2024)
Zingiber, a notable genus within the Zingiberaceae family, is widely distributed throughout Southeast Asia. It encompasses a total of at least 141 species on a global scale, with 25 native species and 30 known taxa identified specifically in Peninsular Malaysia. Of these known taxa, at least 7 are categorised as threatened, 5 are endemic, and the rest remain unassessed regarding their conservation status. This article provides a comprehensive checklist and taxonomic insights for all native Zingiber in Peninsular Malaysia. Remarkably, from the current fieldwork, the discovery of a peculiar Zingiber plant from the northern part of Peninsular Malaysia holds the potential to contribute additional records within this genus. Initially, this species resembles Z. belumense and Z. purpureum in their inflorescence colouration, displaying shades ranging from brownish maroon to dark purple with green bracts, but this newly proposed taxon stands out due to its combination of distinctive traits. An intriguing observation notes the presence of red sap when the leafy shoots were cut and needs further corroboration. This article establishes a provisional taxonomic designation for the newly discovered species, Zingiber sp. (Bahangense130). A comprehensive description supported by robust molecular phylogenetic evidence is currently underway, while brief notes and illustrative images of the proposed taxon are provided within this paper.